Hegel's "Encyclopedia of the philosophical sciences": a critical guide - Stein, Sebastian; Wretzel, Joshua (Cambridge University Press, 2021)
"In 1817, Hegel published a condensed articulation of his basic philosophical commitments, designed to help make his notoriously difficult lectures a bit easier to follow. He titled this compendium the Encyclopedia of the Philosophical Sciences in Basic Outline and, for the rest of his life, made consistent use of it in his classes, constantly amending it until its last, more detailed version was published in 1830. That Hegel called this text an "encyclopedia" was as bold a choice as it was strange. For on the one hand, it of course suggests that Hegel saw his own knowledge and system of philosophy as encyclopedic. But on the other hand, the text also bears no structural resemblance to any other encyclopedia"--
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831 -- Encyklopädie der philosophischen Wissenschaften; Hegel, Georg Wilhelm Friedrich / Enzyklopädie der philosophischen Wissenschaften im Grundrisse